Domains of Political Metaphors in Presidential Speeches - Pasaribu, Truly Almendo (LLT Journal: A Journal on Language and Language Teaching, 2016)
Speeches are products of human minds reflecting ideas and opinions of the speakers. Crystal (1987) mentions that the way people use language does not only give us information about their geographical, ethnic and social background, but it also reflects the type of context in which they are communicating. As an interesting feature of a language, metaphors in political speeches can be powerful and persuasive. This research aimed at finding the source domains of political metaphors in Joko Widodos speeches, namely: his victory speech and his inaugural speech. These speeches were chosen to be analyzed due to their distinct context and setting. To achieve the goal of the study, the paper explicated Lakoff and Johnsons Contemporary Theory of Conceptual Metaphor (1980, 1992). The findings and discussion argue that the speeches use more positive metaphors of unity rather than metaphors of battle or competition. Furthermore, the texts also conceptualize Indonesian political realm as a journey and navigation, which give the audience a sense of progress. The maritime metaphors in particular are abundant in the two speeches because they reflect one of Widodos visions to strengthen Indonesian maritime.